EVALUASI PROGRAM DAURAH (PELATIHAN) TAHSIN DI MARKAZUL QURAN BUKITTINGGI MENGGUNAKAN METODE KIRKPATRICK - Rio Friyadi; Supratman Zakir; Darul Ilmi (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
Evaluation of training results is a very important stage in training because it provides feedback on training eflectiveness that can be used to improve training design. The aim of this research is to analyze the results of the Daurah Tahsin level 1 and level 2 training evaluations from Kirkpatrick Analisys, provide actions that need to be taken in relation to the results of the analysis, and provide suggestions in the form of measuring tools that can help training implementers carry out level 3 evaluations from Kirkpatrick Analisys . The method used in this research is a descriptive analysis method where the data obtained is described and then analyzed. The results of this research were that the majority of training participants were satisfied with the implementation of the Daurah Tahsin training and were able to understand well the materials provided during the Daurah Tahsin training. Improving the quality of trainers and materials tailored to the participants' initial level of understanding are suggestions given to increase the eflectiveness of training. A proposed measuring tool in the form of a questionnaire that can measure, process and analyze the evaluation of Daurah Tahsin training at level 3 of Kirkpatrick Analysis is also provided so that training implementers can measure the impact of this training on improving or increasing the memurajaah (repeating memorization) and ziyadah (increasing memorization) of the participants.